Sistem Pakar Rekomendasi Profesi Berdasarkan Multiple Intelligences Menggunakan Teorema Bayesian - Elvanisa Ayu Muhsina; Nurochman Nurochman (UIN Sunan Kalijaga Yogyakarta, 2017)
Intelligence is perhaps to be the one of the most logical way to determine how smart people is. That fact has always been a problem at job because there are number of job that attract people but require a high GPA for them. Employee with high GPA doesn’t always fit in his skill and work role. They unable to understand and maintain their performance. This expert system is a necessary for recommend job using Intelligence. This research use a Bayesian theorem calculation to find out probability value and job recommendation. The value of MI (Multiple Intelligences)’s user, MI probability to a job and job probability to previous result without any evidence produce a Calculation Variable.Result of the test shows output recommendation as expert system to 81.25% match with expert recommendation. 100% users statistically states the system running well. Expert system usability test shows 80% users strongly agree, 15.7% users agree and 4.3% users are neutral.Keywords: Multiple Intelligences, Profession, Bayesian theorem